Forelimb feathering, soft tissues, and skeleton of the flying dromaeosaurid Microraptor - Maxime Grosmougin; Xiaoli Wang; Xiaoting Zheng; Thomas G. Kaye; Matthieu Chotard; Luke A. Barlow; T. Alexander Deccechi; Michael B. Habib; Juned Zariwala; Scott A. Hartman; Xing Xu; Michael Pittman (BMC Ecology and Evolution)
Abstract Background Microraptor is an essential animal for understanding the evolution of flight in birds and their closest relatives. Recent studies have uncovered evidence of its powered flight potential and details of its diet and ecology. However, we are still missing a thorough description of the anatomy of Microraptor connecting feathers, soft tissues, and osteology together. Here we focus on the forelimbs of ten new Microraptor specimens from the Shandong Tianyu Museum of Nature studied under Laser-Stimulated Fluorescence. We compared our results with extensively studied existing specimens (e.g., IVPP V13352 and BMNHC PH881), other key early paravians (e.g., Anchiornis, Archaeopteryx and Confuciusornis), as well as modern birds to expand what we know about flight origins, and early diverging paravian theropods more generally. Results Plumage was previously only minimally known. Reconstruction of the forewings relied on brief descriptions of the primary and secondary feathers. With the new specimens studied here, we uncovered the whole shape of the wing from the tip of the digits to the proximal end of the ulna, the different layers of feathers, and the number as well as characteristics of each feather type. Skeletal features of the forelimb remain mostly unchanged from previous descriptions, but we bring new information regarding wrist bones and functional implications of humerus and radius features. The most significant advances have been recovered in preserved soft tissues including those of the shoulder, propatagium and postpatagium. In particular, the new specimens of Microraptor help us to understand the impact of the soft tissues on lift generation and cohesiveness of the forewing. Conclusions This study permitted us to recreate the most accurate forewing of Microraptor to date. Taken together, new information on the forelimb anatomy shows that Microraptor shares many of the forewing characteristics of early avialans and modern birds, and helps us to better understand the flight behaviour and ecology of this iconic and unique ‘four-winged’ animal along with its role in flight evolution. These results serve as a starting point to conduct more precise and integrative analyses (e.g., including hindwings and/or tail) on the locomotor behaviours of Microraptor.